2018
DOI: 10.1111/bjh.15646
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor does not impact patient‐reported pain in young adults with sickle cell disease: a multicentre, randomised phase IIb study

Abstract: Summary Ticagrelor is an antiplatelet agent for adults with coronary artery disease. The inhibition of platelet activation may decrease the frequency of vaso‐occlusion crisis ( VOC ) in sickle cell disease ( SCD ). The HESTIA 2 study ( NCT 02482298) randomised 87 adults with SCD (aged 18–30 years) 1:1:1 to twice‐daily ticagrelor 10, 45 mg or placebo for 12 weeks. Numerical decreases fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
(28 reference statements)
0
18
0
Order By: Relevance
“…Prasugrel showed appropriate levels of anti-platelet aggregation compared to healthy patients in ex vivo studies, and was well tolerated by patients, but on a 24-month follow up, patients on the treatment arm failed to show reduction in the frequency of VOC (Heeney et al, 2016;Conran and Rees, 2017). Ticagrelor, in a phase 2b study, was well tolerated, but failed to show effect in the frequency of VOC (Kanter et al, 2019) (ClinicalTrials.gov identifier: NCT02482298). Previous studies have also showed that aspirin as an anticoagulant therapy did not provide benefit over placebo, although it is used as an analgesic in many parts of Africa (Sins et al, 2017).…”
Section: (4) Targeting Inflammationmentioning
confidence: 99%
“…Prasugrel showed appropriate levels of anti-platelet aggregation compared to healthy patients in ex vivo studies, and was well tolerated by patients, but on a 24-month follow up, patients on the treatment arm failed to show reduction in the frequency of VOC (Heeney et al, 2016;Conran and Rees, 2017). Ticagrelor, in a phase 2b study, was well tolerated, but failed to show effect in the frequency of VOC (Kanter et al, 2019) (ClinicalTrials.gov identifier: NCT02482298). Previous studies have also showed that aspirin as an anticoagulant therapy did not provide benefit over placebo, although it is used as an analgesic in many parts of Africa (Sins et al, 2017).…”
Section: (4) Targeting Inflammationmentioning
confidence: 99%
“…[95][96][97] Piroxicam, ticagrelor, and ticlopidine showed modest to disappointing results in reducing the pain of VOC in SCD patients (Table 2). [98][99][100] Although these drugs were largely unsuccessful in reducing acute VOC events, they may possibly provide benefit to chronic organ damage, which has not been studied as an end point.…”
Section: Plateletsmentioning
confidence: 99%
“…There were no discontinuations due to AEs, and reported AEs were mainly due to SCD and not treatment-related [40]. The HESTIA2 study randomized 87 young adults (aged 18-30 years) with SCD in a 1:1:1 ratio to ticagrelor 10 mg, ticagrelor 45 mg, or placebo BID [41]. Patients reported daily pain and analgesic use in an electronic device (eDevice) during the 4-week single-blind run-in placebo period, as well as during the 12-week randomized treatment period.…”
Section: The Hestia Programmentioning
confidence: 99%
“…The study will comprise a screening period of 7-28 days, followed by randomization of eligible patients to double-blind treatment with either ticagrelor or matching placebo for a period of 12-24 months using an Interactive Voice/Web Response System. Body-weight adjusted ticagrelor doses (15 mg: ≥ 12 to ≤ 24 kg body weight, 30 mg: > 24 to ≤48 kg body weight, or 45 mg: > 48 kg body weight BID) have been identified based on PK/PD modeling and simulation of phase 2 data (HESTIA1 and HESTIA2) [40,41]. For any patient with weight gain during the study period exceeding the upper weight-limit bands of ≥ 27 kg or ≥ 54 kg, treatment dose will be increased according to the next higher weight band.…”
Section: Study Treatment Protocol and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation